Diversity of Brazilian Fungi - Maia, Leonor C.; Carvalho Júnior, Aníbal A. De; Cavalcanti, Laise De H.; Gugliotta, Adriana De M.; Drechsler-santos, Elisandro R.; Santiago, André L.m. De A.; Cáceres, Marcela E. Da S.; Gibertoni, Tatiana B.; Aptroot, André; Giachini, Admir J.; Soares, Adriene M. Da S.; Silva, Allyne C.g.; et al. (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2015)
Abstract Knowledge about the Brazilian fungal diversity was, until 2010, recorded in few taxonomy and ecology publications, as well as in a handful of species lists. With the publication of the Catálogo de Plantas e Fungos do Brasil and the continued availability of an online list, it has been possible to aggregate this dispersed knowledge. The version presented here adds 2,111 species names to the 3,608 listed in 2010. A total of 5,719 species of fungi distributed in 1,246 genera, 102 orders and 13 phyla represents a considerable increase over the last five years, when only 924 genera and 78 orders were registered. Basidiomycota (2,741 species in 22 orders) and Ascomycota (1,881 species in 41 orders) predominate over other groups. The Atlantic Rainforest has the largest number of records, with 3,017 species, followed by Amazon Rainforest (1,050), Caatinga (999), Cerrado (638) and Pampa and Pantanal with 84 and 35 species, respectively. The Northeast region has the greatest richness (2,617 species), followed by Southeast (2,252), South (1,995), North (1,301) and Central-West (488 species). Regarding the States of the Federation, São Paulo with 1,846 species, Pernambuco with 1,611 and Rio Grande do Sul with 1,377 species are the most diverse.

Resumo Até 2010, o conhecimento sobre a diversidade de fungos do Brasil estava registrado em publicações esparsas de taxonomia e ecologia e em algumas poucas listas de espécies. Com a publicação do Catálogo de Plantas e Fungos do Brasil, e a disponibilização da lista online, tem sido possível agregar o conhecimento disperso. A versão ora apresentada acrescenta 2.111 nomes de espécies aos 3.608 listados em 2010. São citadas 5.719 espécies de fungos distribuídas em 1.246 gêneros, 102 ordens e 13 divisões, consistindo em considerável aumento em relação a 2010, quando estavam registrados 924 gêneros e 78 ordens. Predominam os Basidiomycota (2.741 espécies, em 22 ordens) e Ascomycota (1.881 espécies, em 41 ordens). A Mata Atlântica possui a maior quantidade de registros, com 3.017 espécies, seguido pela Amazonia (1.050), Caatinga (999), Cerrado (638) e Pampa e Pantanal com 84 e 35 espécies, respectivamente. A região Nordeste tem a maior riqueza (2.617 especies), seguida pelo Sudeste (2.252), Sul (1.995), Norte (1.301) e Centro Oeste (488 espécies). Em relação aos Estados da Federação, São Paulo (1.846 espécies), Pernambuco (1.611) e Rio Grande do Sul (1.377) são os mais diversos.
Keywords: Taxonomy; mycology; brazilian regions; Taxonomia; micologia; regiões brasileiras